Perkembangan Sosioemosional dan Konteks Sosial - Nasution, Fauziah; Pitriana, Eka Riski; Berutu, Syanti Laura; Hasibuan, Yuli Anisah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Children's socio-emotional development is an important indicator of children's growth and emotional development is an important indicator of their overall social and emotional growth. The process by which children's behavior changes to conform to the norms of the environment in which they live is called social development, which is a change in behavior. children to conform to the norms of the environment in which they live is called social development. The complicated condition known as children's emotional development is described as feelings or mental vibrations that occur simultaneously with changes in behavior and is characterized by biological changes.